Locally advanced breast cancer in elderly patients - Hornová, Jana; Bortlíček, Zbyněk; Májková, Petra; Abrahámová, Jitka; Kordíková, Drahomíra; Donátová, Zuzana; Kupec, Martin; Boublíková, Ludmila; Dvořák, Josef; Zapletal, Radek; Büchler, Tomáš (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2017)
BACKGROUND: Although locally advanced breast cancer (LABC) is more common in the elderly population, there is little data on the clinical characteristics and survival of these patients. The aim of the present study was to compare different factors affecting survival in elderly patients with LABC. METHODS: Retrospective analysis was carried out on a cohort of 80 patients aged 70 to 96 years, diagnosed with LABC defined as T3 N1, T4 N0, any N2 or N3, and M0. The prognostic impact of selected clinical parameters including age, comorbidities, tumour grade, HER2 status, tumour stage, local therapies, and systemic treatments was studied. RESULTS: The median age of the patients was 79 years. The majority (n=53; 66%) had at least one significant comorbidity according to the Charlson score evaluation. The median overall survival was 50.6 months. As expected, hormonal therapy was the dominant mode of systemic treatment, but 24% also received at least one line of chemotherapy. Local therapies including surgery and/or radiotherapy were applied in 58% of patients. CONCLUSIONS: The diagnosis of LABC in the elderly is associated with poor prognosis. Age and serious comorbidities were negative prognostic factors.
Keywords: přežití bez známek nemoci; prognóza; lokální recidiva nádoru; Neoplasm Recurrence, Local; Disease-Free Survival; Prognosis; nádory prsu; senioři nad 80 let; lidé; senioři; retrospektivní studie; Female; Aged; Breast Neoplasms; Retrospective Studies; Aged, 80 and over; ženské pohlaví; Humans